2016
DOI: 10.1016/j.jelectrocard.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmia burst is an independent indicator of larger infarct size even in optimal reperfusion in STEMI

Abstract: In the event of MBG 3, VA bursts were associated with significantly larger infarct size even if optimal epicardial and microvascular reperfusion was present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The same pathophysiology that exists in IR injury, e.g., apoptosis and mitochondrial dysfunction, drives many forms of arrhythmias, including the main type, accelerated idioventricular rhythms [47]. Thus, the two conditions complement each other and, together, contribute to larger infarct size, meaning more myocyte death and decreased ventricular functioning [47][48][49][50][51][52][53]. Notably, studies support that reperfusion without arrhythmia has a smaller infarct size regardless of the same initial areas at risk [47][48][49][50][51][52].…”
Section: Role Of Cardiac Mir-1 In Ir Injurymentioning
confidence: 99%
“…The same pathophysiology that exists in IR injury, e.g., apoptosis and mitochondrial dysfunction, drives many forms of arrhythmias, including the main type, accelerated idioventricular rhythms [47]. Thus, the two conditions complement each other and, together, contribute to larger infarct size, meaning more myocyte death and decreased ventricular functioning [47][48][49][50][51][52][53]. Notably, studies support that reperfusion without arrhythmia has a smaller infarct size regardless of the same initial areas at risk [47][48][49][50][51][52].…”
Section: Role Of Cardiac Mir-1 In Ir Injurymentioning
confidence: 99%
“…31 This increase in arrhythmias include higher risk for ventricular arrhythmias with larger infarct size. 32 However, there is no conclusive evidence that the rate of arrhythmias are higher in patients with STEMI versus patients with non-STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…This connection is supported by previous findings by our group. [3][4][5][6][7][8][9] We found, in several independent cohorts, the presence of a 'burst' of ventricular reperfusion arrhythmias (VA burst) to be related to clinically significant larger infarct size. This increase remained while correcting for other known factors of increased infarct size.…”
Section: Correlation Between Fatal Reperfusion Injury and Reperfusionmentioning
confidence: 96%
“…reopening of the infarct vessel, more recent studies have shown that reperfusion without arrhythmias resulted in smaller infarcts in spite of equal initial areas at risk. [3][4][5][6][7][8]…”
Section: Reperfusion Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation